Fibroblast growth factor 3 promotes spontaneous mammary tumorigenesis in Tientsin albino 2 mice via the FGF3/FGFR1/STAT3 pathway - Chen, Lankai; Zhang, Xipeng; Liu, Guisheng; Chen, Shuo; Zheng, Minying; Zhu, Siwei; Zhang, Shiwu (Frontiers in Oncology, 2023)
Tientsin albino 2 (TA2) mice can develop spontaneous breast cancer (SBC), which is associated with multiple pregnancies and infection with the mouse mammary tumor virus (MMTV). To elucidate the molecular mechanism of MMTV, which leads to the development of SBC in TA2 mice, the integration site of MMTV in TA2 SBC was identified using whole-genome sequencing. The expression of fibroblast growth factor 3 (FGF3) in SBCs and normal breast tissues was compared. The primary cell line, TA-1106, derived from SBC, was cultured. The proliferation, cell cycle, migration, invasion, and tumorigenicity abilities, as well as the expression of epithelial-mesenchymal transition-related proteins, phosphorylated STAT3, and phosphorylated Akt, were assessed in MA-891cell line from TA2 and TA-1106 cells after FGF3 knockdown. The binding of FGF3 to FGF receptor 1 (FGFR1) was determined by co-immunoprecipitation. Additionally, the relationship between STAT3 and Akt phosphorylation was investigated using a small molecule inhibitor and STAT3 knockdown. Results of this study showed that MMTV integrated upstream of the FGF3 gene, and the FGF3 protein was highly expressed in TA2 SBCs. FGF3 knockdown in MA-891 and TA1106 decreased their proliferation, migration, and invasion abilities, affected the cell cycle and expression of epithelial-mesenchymal transition-related proteins, and inhibited the growth of animal xenografts. FGF3 binds to FGFR1, and either FGF3 or FGFR1 knockdown decreases STAT3 and Akt phosphorylation levels. Inhibition of phosphorylation or expression of STAT3 resulted in decreased Akt phosphorylation levels. Inhibition of Akt phosphorylation also results in decreased STAT3 phosphorylation levels. Furthermore, treatment of MA-891 and TA-1106 cells with Wortmannin or Stattic caused FGFR1 upregulation in addition to inhibiting Akt or STAT3 phosphorylation. In conclusion, FGF3 plays an important role in the development of SBC in TA2 mice and is involved in the FGF3/FGFR1/STAT3 signaling pathway. Inhibition of STAT3 or Akt phosphorylation promoted the expression of FGFR1.